Curcumenol Mitigates the Inflammation and Ameliorates the Catabolism Status of the Intervertebral Discs In Vivo and In Vitro via Inhibiting the TNFα/NFκB Pathway - Yang, Xiao; Li, Baixing; Tian, Haijun; Cheng, Xiaofei; Zhou, Tangjun; Zhao, Jie (Frontiers in Pharmacology, 2022)
Low back pain (LBP) caused by intervertebral disc degeneration (IVDD) is accredited to the release of inflammatory cytokines and following biomechanical and structural deterioration. In our study, we use a plant-derived medicine Curcumenol to treat IVDD. Cell viability test was carried out to evaluate the possibility of using Curcumenol. RNA seq is used to determine relative pathways involved with Curcumenol addition. Using TNFα as trigger of inflammation, the activation of NF-κB signaling pathway and expression of MMP family was determined by qPCR and western blotting. Nucleus pulposus (NP) cells and the rats’ primary NP cells were cultured. The catabolism status was evaluated by ex-vivo model. Lumbar instability mouse model was carried out to show effects of Curcumenol in vivo. In general, RNA seq revealed that multiple signaling pathways changed with Curcumenol addition, especially the TNFα/NF-κB pathway. So, NP cells and primary NP cells were induced to suffer inflammation with activated TNFα/NF-κB signaling pathway and increased expression of MMP family, such as MMP3, MMP9 and MMP13, which would be mitigated by Curcumenol. Owing to the protective effects of Curcumenol, the height loss and osteophyte formation of disc could be prevented in ex-vivo culture model and Lumbar instability model in vivo.